READING STORYBOOKS ALOUD TO FACILITATE ELEMENTARY STUDENTS’ ENGLISH PRONUNCIATION LEARNING - Elis Homsini Maolida; Jauhar Helmie; Rahmalia Irvi Khoerunnisa (Universitas Suryakancana, 2026)
Pronunciation is often recognized as one of the most challenging aspects of English learning and requires instructional approaches that provide interactive and meaningful practice. Reading storybooks aloud offers opportunities for young learners to develop pronunciation through contextualized language use and repeated exposure to spoken English. This study aimed to explore the learning process and students’ responses to learning English pronunciation through reading storybooks aloud. The participants were fourth-grade students at an elementary school in West Java, Indonesia. Employing a qualitative descriptive design, the data were collected through classroom observations and semi-structured interviews. The findings revealed that students’ pronunciation learning through reading storybooks aloud occurred through several interconnected stages. These included pre-reading activities, in which students engaged with storybook covers, titles, illustrations, and key vocabulary; teacher-led reading aloud that provided pronunciation models; guided repetition of sentences; story retelling to reinforce understanding; and pronunciation rehearsal through group and individual reading aloud accompanied by immediate teacher feedback. These stages facilitated students’ engagement with English pronunciation in a meaningful and supportive learning environment. The results indicate that reading storybooks aloud was implemented effectively and created an enjoyable learning atmosphere. Most students demonstrated improved pronunciation accuracy and responded positively to the activities, particularly when using illustrated storybooks. However, a small number of students experienced pronunciation difficulties due to limited focus and insufficient practice. Overall, the study suggests that reading storybooks aloud is a beneficial pedagogical approach for supporting English pronunciation development among elementary school students.